Intersectionality Between CEDAW and Culture in Tonga’s Gender Development Efforts - Iklilah Qotrinnada (Education and Sociedad Journal, 2025)
The South Pacific Region is known for its slow progress in gender equality and ranks relatively low on the GII (Gender Inequality Index). However, Tonga, as the only part of that region that has not ratified CEDAW (Convention on the Elimination of All Forms of Discrimination Against Women), has experienced significant fluctuations in its GII rating. After improving from 0.460 in 2015 to 0.354 in 2020, Tonga’s GII worsened to 0.444 in 2023, placing it 92nd out of 193 countries (UNDP, 2025). This phenomenon raises a question about the reasons for the reversal in Tonga’s Gender Inequality Index trajectory despite the government’s domestic gender policy efforts and the absence of CEDAW ratification. This research uses a descriptive analytical method and gathers data from various sources such as reputable articles, books, government reports, international organizations’ reports, and other sources known to be part of library research and documentation research. This study uses Liberal Feminism with Intersection Approach to analyze the phenomenon. Findings show that Tonga’s earlier success in improving GII was due to the good government effort to acknowledge the overlapping problem between CEDAW and Cultural Identity ‘anga fakatonga’ and transform it into a domestic gender policy that is appropriate to Tonga’s Socio-Cultural Conditions. However, the recent GII deterioration suggests that structural barriers, including limited women’s political representation at 7.1% and declining female labor force participation, continue to constrain progress. This study will help the government and policymakers to understand the importance of acknowledging intersectionality within gender problems and turn it into a supporting factor in gender development efforts.